Design method for a bionic wrist based on tensegrity structures. Issue 2 (19th April 2020) - Sun, Jianwei; Cao, Xuemin; Song, Guangsheng
Abstract : The traditional bionic upper limb structure design is limited by the motion pair and cannot guarantee the flexibility of the mechanical structure. The tensegrity structure has the characteristics of high deformability, strong self‐adaptability, and resistance to multi‐directional impact. According to the biological characteristics of the upper limbs of the human body, an anatomical study is performed on the upper limb wrist joints that achieve adduction/abduction, flexion/extension, to obtain the relationship between the movements of the related bones and muscles, and to simplify the shape and structure of the wrist. Equivalent mapping of a mechanical model based on two‐bar tensile properties. Through the contraction and stretching of the spring, the movement characteristics of the human muscles are realised, and the optimised bionic upper limb wrist tensioning robot without motion pair is further obtained. Adams simulation is used to verify that the bionic tensile wrist can simulate the change movement of the human wrist. The experimental platform was built and a physical prototype was made and the prototype was tested. The results show that the bionic tensile wrist can realise the adaptive motion characteristics of the human wrist well and stably, which proves the validity and feasibility of this design method.